Islamic Philanthropy Institutions and the Welfare of the People - Lestari, Rini; ., Nurleli; Pradifta, Radhitya (KnE Social Sciences, 2023)
The potential of Islamic community philanthropic funds worldwide is estimated to range from US250 billion to US1 trillion. However, effectively managing these funds to achieve optimal results remains the greatest challenge. A joint research effort between Baznas and various institutions indicates that the potential for zakat in Indonesia reached IDR 327.6 trillion in 2020. Unfortunately, the actual realization of zakat collection was only around Rp 71.4 trillion or approximately 21.7 percent of the potential amount. This study aims to assess the capabilities of Islamic philanthropic institutions in Indonesia, particularly in Bandung City, West Java, in managing philanthropic funds to enhance the welfare of the people in Indonesia. The analysis method used in this research is descriptive statistics. The subsequent research team will elaborate on how these Islamic philanthropic institutions in Bandung are able to implement programs to improve the well-being of the community. The research findings demonstrate that these institutions have been successful in creatively and innovatively implementing and managing programs that contribute to the realization of community welfare. Keywords: Islamic philanthropy institution, program-program, the welfare’s people